Ted in a red bed - Cox, Phil Roxbee; Cartwright, Stephen; Tyler, Jenny (London : Usborne ; Tulsa, Okla. : EDC Pub., 1999)
Ted has a strange dream when he buys a red bed and falls asleep right in the store.
"Simple phonics reader"--Cover.
Lift the flap pages.
1.0.
K-3
K-3
K-3
Keywords: Toy and movable books -- Specimens; Teddy bears -- Fiction; Toy and movable books; Teddy bears -- Fiction; Toy and movable books